Metodologia para suporte ao processo de enquadramento dos cursos dágua superficiais considerando curvas de permanência de qualidade e processo de autodepuração - Calmon, Ana Paula Santos (2015)
Lack of actions regarding to water quantity and quality management leads to water and environmental stress situations, resulting in damage to of hydro ecosystems integrity. The river classes establishment is an environmental planning instrument, integrating water system quality and quantity aspects in hydrographic basins. In this context, the present work aims to propose a methodology to support the establishment of Brazilian CONAMA 357/2005 rivers water quality classes, based on joint analysis of quality durationcurves and rivers' self-purifying capacity. The research was developed in the Pardo river watershed, an important water course for the southern portion of the Espírito Santo State, taking into consideration sanitary sewage as the only pollutant loads source. In order to compose different water quality simulation scenarios, three sewage treatment sceneries associated to distinct removal of Biochemical Oxygen Demand (BOD) efficiency were established, two organic loads abatement conditions and three analysis horizons (2014, 2020 and 2030). The QUAL-UFMG model was used for the evaluation of Pardo river watershed water courses self-purifying capacity, having simulated BOD and dissolved oxygen (DO) parameters, considering as reference flow with 90% permanence (Q 90). Quality duration curves were produced for the DBO 5,20 parameter associated to the environmental patterns established by CONAMA Resolution Nº 357/2005 for the Class 1, 2 and 3 rivers. The applied methodology considered in the current work enabled estimation of the quality conditions compatibility probabilities within the Pardo River, in different control sections taken into consideration for different environmental patterns. Additionally, it was verified that the consideration of self-purifying capacity of Pardo watershed rivers caused an abatement of the organic loads in such levels that influence the compliance frequency with water quality standards related to DBO 5,20 parameter, affecting basin water courses water quality classes establishment perspective. The obtained results indicate the relevance of self-purifying modeling consideration for evaluation of superficial water bodies quality for rivers water classes establishment and indicate that the non-deterministic view offered by the duration curves would facilitate the decision process making about in progressive water quality objectives establishment of progressive water quality objectives.